Sequestering sequestosome 1 via S-acylation in autophagy, Huntington disease, and beyond - Y Alshehabi; F Abrar; D.D.O Martin (Autophagy Reports)
Protein mislocalization and aggregation are hallmark features in neurodegeneration. As proteins mislocalize, proteostasis deficiency and protein aggregation typically follow. Autophagy is a crucial pathway for the removal of protein aggregates to maintain neuronal health, but is impaired in various neurodegenerative diseases, including Huntington disease (HD). We identified S-acylation, a reversible lipid modification of proteins, as an important regulator in protein trafficking and autophagy. SQSTM1 (sequestosome 1/p62) is an essential selective autophagy receptor for the sequestration of ubiquitinated cargoes within autophagosomes and subsequent delivery into lysosomes for degradation. Recently, we reported that S-acylation of SQSTM1 at the di-cysteine motif C289,290 directs SQSTM1 to lysosomes. We further showed that SQSTM1 S-acylation is significantly reduced in brains from both HD patients and mouse HD model, which may result in the cargo sequestration defect within autophagosomes in HD. Treatment with palmostatin B, a deacylation inhibitor, significantly increases SQSTM1 localization to lysosomes. Our work highlights SQSTM1 S-acylation as a novel potential therapeutic strategy in HD. As a crucial autophagy component, our work suggests S-acylation of SQSTM1 may have a broader role in neurodegeneration.